This time with feeling: recommendations for full-bodied reporting of research on dance - Barnstaple, Rebecca Elizabeth; Laurita-Spanglet, Jessie; Fanning, Jason; Soriano, Christina; Hugenschmidt, Christina E. (Frontiers in Cognition, 2024)
Collaborations that employ methods from arts and sciences to address research questions through multimodal study design are becoming more frequent, as it is increasingly apparent that complex challenges require transdisciplinary solutions. These different modalities rely on interdisciplinary exchange while involving unique expertise in associated delivery practices. In human subject driven scientific research specifically, guidelines for arts-based interventions deserve detailed reporting to allow for fidelity, replicability, and uptake of innovation and results. Details such as frequency, duration, delivery method, expected outcomes, historical precedence, and instructor training are crucial, along with nuanced descriptions pertaining to embodied aspects of specific dance or movement style(s) and adaptations made for the population or study design. This Perspective Paper outlines the current state and challenges of reporting on dance interventions and makes recommendations based on our experience as teaching artists who work in research settings alongside researchers who collaborate with dance professionals.